Seasonal abundance of Tetranychus urticae and Amblyseius swirskii (Acari: Tetranychidae and Phytoseiidae) on four strawberry cultivars - Shimaa F. Fahim; El-Sayed M. El-Saiedy (Persian Journal of Acarology)
The population abundance of Tetranychus urticae Koch and its naturally occurring phytoseiid mite, Amblyseius swirskii Athias-Henriot on four strawberry cultivars (029, Fortona, Markez and Wanter star) were studied during 2017/2018 and 2018/2019 seasons. In both studied seasons, the population of T. urticae was observed from mid-October, and still recorded until the beginning of May. The peaks of infestation appeared in February or March (according to the cultivar) then declined later until the end of the study. The predatory mite (A. swirskii) initially appeared in January 2018 and 2019, while its population's peaks were observed in March on the four cultivars. In the two studied seasons, 029 cultivar was infested with the maximum numbers of T. urticae followed by Markez and Fortona cultivars, while Wanter star cultivar had the lowest infestation. In the present study, as the foliar concentrations of alkaloids and phenolic compounds increased, the cultivar infestation with T. urticae decreased. In all cultivars, a positive correlation between the populations of A. swirskii and T. urticae was observed. The present work may be considered useful to develop a successful management program of T. urticae, a serious pest of strawberry.